2019
DOI: 10.1111/tbj.13482
|View full text |Cite
|
Sign up to set email alerts
|

Time from Completion of Neo‐adjuvant Chemotherapy to Surgery: Effects on Outcomes in Breast Cancer Patients

Abstract: There is no consensus on the ideal time interval between the completion of neo‐adjuvant chemotherapy (NAC) and definitive surgery for patients with breast cancer. This study sought to determine the ideal time interval from completion of systemic therapy to surgery in an attempt to define a best practice. A retrospective analysis of all patients undergoing NAC for Stage I‐III breast cancer from 1998‐2010 was undertaken. Analysis of all demographic and clinical information was performed, with emphasis on interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In our subgroup analysis ,patients who received surgery with TTS > 4 weeks had a worse prognosis.Using TTS < 4 weeks as a reference time interval,the pooled HRs for OS and DFS/RFS were 1.39 (95%CI:1.18-1.63) and1.33(95%CI:1.16-1.53),respectively. In terms of DFS/RFS, as shown in gure 5, there was no different in the patients who underwent surgery in 4-6weeks or > 6 weeks,the combined HRs were 1.24 (95CI%:0.69-2.22,I 2 =92.8%) and 1.84 (95CI%:0.89-3.79,I 2 =81.2%),respectively,and the differences did not reach statistical signi cance.As for OS,the pooled HRs for the breast cancer patients who underwent surgery with TTS 4-6weeks and > 6 weeks were 0.87(95%CI: 0.67-1.10) and 1.34 ((95%CI:1.04-1.71),respectively.As can be seen,two studies explored the relationship between TTS 4-6 weeks and OS [13,18], the pool HR revealed that patients with TTS 4-6 weeks reduced in the risk of death by 13%,with no signi cant heterogeneity(I 2 =0%,P=0.69),while the difference was not statistically signi cant,so the results should be interpreted cautiously.The pooled HR for the breast cancer patients who underwent surgery with TTS > 8 weeks were 1.49(95%CI: 1.05-2.12,I 2 =0%),and this difference was statistically signi cant( gure 4).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In our subgroup analysis ,patients who received surgery with TTS > 4 weeks had a worse prognosis.Using TTS < 4 weeks as a reference time interval,the pooled HRs for OS and DFS/RFS were 1.39 (95%CI:1.18-1.63) and1.33(95%CI:1.16-1.53),respectively. In terms of DFS/RFS, as shown in gure 5, there was no different in the patients who underwent surgery in 4-6weeks or > 6 weeks,the combined HRs were 1.24 (95CI%:0.69-2.22,I 2 =92.8%) and 1.84 (95CI%:0.89-3.79,I 2 =81.2%),respectively,and the differences did not reach statistical signi cance.As for OS,the pooled HRs for the breast cancer patients who underwent surgery with TTS 4-6weeks and > 6 weeks were 0.87(95%CI: 0.67-1.10) and 1.34 ((95%CI:1.04-1.71),respectively.As can be seen,two studies explored the relationship between TTS 4-6 weeks and OS [13,18], the pool HR revealed that patients with TTS 4-6 weeks reduced in the risk of death by 13%,with no signi cant heterogeneity(I 2 =0%,P=0.69),while the difference was not statistically signi cant,so the results should be interpreted cautiously.The pooled HR for the breast cancer patients who underwent surgery with TTS > 8 weeks were 1.49(95%CI: 1.05-2.12,I 2 =0%),and this difference was statistically signi cant( gure 4).…”
Section: Resultsmentioning
confidence: 96%
“…Data synthesis:A total of four hundred and ve potentially relevant publications were found according to our initial search strategy,one hundred and sixteen publications from PubMed/Medline,two hundred and eighty-nine publications from Embase.There were three hundred and one publications after duplicate publications were removed;of these,we excluded two hundred and sixty-eight articles because the title or abstract did not meet the eligibility criteria.Eight systematic reviews,four studies on metastatic breast cancer,and eleven non-neoadjuvant chemotherapy were further excluded. Eventually,nine studies were identi ed as eligible for our analysis,including nine independent studies for OS [11][12][13][14][15][16][17][18][19],six studies for RFS [11,12,[15][16][17][18],and three for DFS [13,14,19].The ow chart of the literature search and study selection is shown in gure 1. Subsequently,subgroup analysis was performed based on different time intervals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important issue is the management of patients who have currently completed neoadjuvant therapy and are waiting for surgery. Although many studies have suggested that delayed surgical treatment could lead to poor prognosis in breast cancer patients, the delay between neoadjuvant therapy and surgery has been ignored by many prospective clinical trials of neoadjuvant chemotherapy [31,34]. At present, the physical condition of patients receiving neoadjuvant therapy needs 2 to 3 weeks to recover from the toxic reactions of neoadjuvant regimens, therefore surgery is typically performed during this time.…”
Section: Delay Of Surgical Treatment In Early-stage Breast Cancer Patmentioning
confidence: 99%
“…However, the influence of delayed surgery on prognosis of breast cancer patients was unclear. Retrospective studies showed that an interval of less than 3 weeks tended to improve the prognosis of breast cancer patients, and an interval of less than 6 weeks did not affect RFS (relapse-free survival), LRFS (locoregional recurrence-free survival) or OS in breast cancer patients [34][35][36]. Therefore, patients receiving neoadjuvant chemotherapy should undergo surgery as soon as possible.…”
Section: Delay Of Surgical Treatment In Early-stage Breast Cancer Patmentioning
confidence: 99%